PENGARUH SANKSI PERPAJAKAN, PELAYANAN FISKUS, PENGETAHUAN DAN PEMAHAMAN PERPAJAKAN, KESADARAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Esti Rizqiana Asfa I.; Wahyu Meiranto (Diponegoro Journal of Accounting, 2017)
The purpose of this study was to analyze the factors that affect to tax compliance, especially compliance of individual taxpayers. Factors that are expected to have an influence on an individual taxpayers compliance is tax penalties, service tax authorities, knowledge and understanding of tax, tax awareness.The populations used in this study is the individual taxpayer that listed in KPP Semarang Barat. Sampling was done by convenience sampling technique. The number of samples was determined as many as 100 people from the number of individual taxpayers that listed in KPP Semarang Barat. Primary data collection method using questionnaire. Data analysis techniques performed by hypothesis testing using multiple linear regression method. The results of this study indicate that tax penalties not significantly positive related to tax compliance. While service tax authorities, knowledge and understanding of tax, tax awareness are significantly positive related to tax compliance.